Type of Packaging Bags and their Impacts on the Post-Harvest Quality of Sorghum (Sorghum bicolor L.) - Dahlan, Sakinah Ahyani; Saman, Widya Rahmawaty (Program Studi Teknologi Hasil Pertanian, Politeknik Gorontalo, 2025)
The primary objective of this study is to explore how different packaging bag types affect the storage duration of sorghum seeds during the post-harvest phase of sorghum (Sorghum bicolor L.). The storage process plays a pivotal role in determining the quality of sorghum seeds until they are ultimately consumed. This significance arises from the heightened risk of fungal infestation during this stage, primarily influenced by storage conditions, including the type of packaging utilized. The research involves identifying fungi, specifically belonging to the Aspergillus sp. group, known for their association with storage fungi. These fungi were directly isolated from dried sorghum seeds. The study follows a descriptive methodology, and data analysis is performed using SPSS Descriptive. The presence of fungi from the Aspergillus sp. group in all sorghum samples suggests that the chosen packaging was ineffective in safeguarding the sorghum seeds during storage.